Analysis of Accruals Earnings Management Using the Jones Model. The Case of Romania Listed Companies - Georgiana Burlacu; Ioan-Bogdan Robu (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- To what extent earnings management operations are used by Romanian entities listed on a regulated market and what is the impact of these operations on the quality of reported financial information? Motivation- The financial statements reported by each entity are intended to provide useful information all the users, they are intended to describe clearly and honestly presents the financial position and performance and cash flows respectively. There are cases where, out of a desire to gain the trust of stakeholders (investors and other equity providers), some entities tend to commit manipulations in financial reporting using earnings management. Idea- The study aims to assess the extent to which the operations of earnings management are used by the Romanian entities listed on a regulated market and the impact of these operations on the quality assurance of the reported financial information. Data- This study was conducted based on the information collected from the annual financial statements of the entities that are listed on the Bucharest Stock Exchange, for the period between 2019-2021 Tools- The collected data were analyzed using the Jonse model based on the linear regression analysis. Findings- Using the Jones model based on the linear regression analysis, the results of the study indicate a distortion of the results presented by the analyzed companies, a solid reason being given by the negative effects of the Covid-19 pandemic with a strong impact on the economic environment. Contribution- This study provides an overview of the concept of earnings management based on information from the specialized literature. The analysis of earnings management practices was undertaken on the listed entities in Romania.
Keywords: C59; M41; 650; earnings management; discretionary accruals; capital market; financial statement